PENGARUH PEMBELAJARAN EKONOMI TERHADAP SIKAP SOSIAL SISWA KELAS XI IPS MAN 2 PONTIANAK - Ari, Zul; GS, Bambang; Rosyid, Rum R (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the " The influence of the social Attitude towards economic studies Students of Class XI IPS MAN 2 Pontianak".Â  the method used is descriptive method quantitative correlation with the form of research studies, date source this study is a student of Class XI IPS MAN 2 Pontianak. with a total population of 78 students because using a systematic sample drawn then sample using the number of absence students who have an even number so that the sample in this study was 40 students. Data taken with the technique of direct observation and indirect communication techniques (Questionnaire/question form). These results indicate that economic studies generally 75.17% enter the category either, as for the sub-sub indicators of economic studies as follows: interest in economic studies of 75.33% fall into the category of good, the motivation to follow the process economic studies of 78.4% in the category of good, student involvement in the learning process of the economy of 72.41% entered the category of good, whereas social attitudes in General of 75.57% entered high category. As for the sub-subsection of social attitude indicator as follows: honesty 76.25% in the high category, discipline 75.66% in the high category, the responsibility of 76.63% in the categories high, and care 73.16% in the high category.Â Keywords: Economic Studies, Social Attitudes, Students